Considerations for nursing research after the COVID-19 pandemic - McKenna, Lisa (Indonesian Contemporary Nursing Journal (ICON Journal), 2023)
The COVID-19 pandemic impacted on nursing in a variety of ways. Many parts of the world experienced long-term lockdowns and what work could be done remotely was undertaken that way. For those nurses engaged in research activities, particularly clinical nursing research, it presented immense challenges. Questionnaire-based research had to be moved exclusively online, while interview-based research was managed using videoconference facilities and making some qualitative research approaches requiring participant observation more difficult. Being able to recruit participants for research was further challenged as researchers were unable to recruit in person and needed to resort to a multitude of online approaches such as using social media platforms. As a result of impacted recruitment, many researchers needed to report their research as being unable to meet quality measures such as sample size calculations or data saturation. This particularly impacted research students with time pressures to complete, and report on, their studies. Similarly, they needed to acknowledge in their study limitations how the pandemic had impacted on their research.